Hepatosplenic Hodgkin lymphoma without lymphadenopathy following reversible methotrexate-associated lymphoproliferative disorder. Issue 2 (4th March 2017) - Tsukazaki, Yuki; Shinohara, Tsutomu; Tanaka, Kumiko; Naruse, Keishi; Iwahara, Yoshihito; Inoue, Shuji
Abstract : Lymphoproliferative disorders (LPDs) occur more frequently in rheumatoid arthritis (RA) patients treated with immunosuppressive agents than in the non-RA population. However, the various forms of disease progression have not yet been elucidated in detail. We encountered a case of Epstein–Barr virus (EBV)-positive atypical polymorphous LPD in the cervical and intraabdominal lymph nodes with hepatosplenomegaly in an 88-year-old female with RA who had taken infliximab and methotrexate (MTX) for six years. Although spontaneous remission occurred following the withdrawal of infliximab and MTX, reversible LPD evolved into hepatosplenic Hodgkin lymphoma without lymphadenopathy presenting as a cholestatic febrile illness. Our findings suggest that the recurrent lesions of MTX-associated LPDs may not always coincide with the primary lesion and may present unexplained findings based on various extranodal diseases.